2011
DOI: 10.1016/j.midw.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the quality of documented care given by Swedish midwives during birth

Abstract: Objective: to measure the extent documented Swedish midwifery care for low risk labour and birth followed WHO's recommendations for care in normal birth and to compare midwifery care given to women who's labours could be classified as low and high risk.Study design: A retrospective examination of midwifery and medical records, 144 from women with low risk births and 54 from women with high risk births, for aspects of pregnancy, labour and birth using a validated instrument based on WHO's recommendations.Settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This may also reflect Swedish midwives risk perception in the process of normal labour. In a recently published study from Sweden with the aim to measure the extent to which documented midwifery care in women with low-risk labour and birth followed WHO's recommendations, it was found that interventions such as routine use of intravenous catheter, administration of oxytocin and use of CTG for longer periods during labour was frequently used during labour also in low-risk women (Kvist et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This may also reflect Swedish midwives risk perception in the process of normal labour. In a recently published study from Sweden with the aim to measure the extent to which documented midwifery care in women with low-risk labour and birth followed WHO's recommendations, it was found that interventions such as routine use of intravenous catheter, administration of oxytocin and use of CTG for longer periods during labour was frequently used during labour also in low-risk women (Kvist et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers collected data for the research using a questionnaire that was developed based on the pertinent literature ( 19 , 20 ) , and assessed using the Bologna score. The questionnaire’s 36 items probed the women’s sociodemographic and obstetric characteristics; whether their pregnancies had been planned and wanted; whether they had received antenatal care; their height and weight; smoking status; cervical dilation upon admittance to hospital; whether an enema, epidural anesthesia, vacuum or episiotomy had been performed during labor; and the baby’s Apgar score in the fifth minute.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, two instruments have been developed based on WHO's recommendations: the Bologna Score (Chalmers and Porter, 2001) and an audit instrument (Sandin-Bojö et al, 2004). Both instruments have been used by Sandin-Bojö et al (2006, 2007 and Sandin-Bojö and Kvist (2008) and the audit instrument has been used by several researchers, among these Hashimoto (2007) and Kvist et al (2011). Studies have shown that the instruments are useful for evaluation and identification of areas of improvement, although they have not been used in a developing country.…”
Section: Introductionmentioning
confidence: 99%